The phenotypic, genotypic and pathogenicity comparison of Edwardsiella ictaluri Indonesian local isolates causing enteric septicemia of catfish. (18th April 2022) - Purwaningsih, Uni; Sukenda, Sukenda; Lusiastuti, Angela M.; Alimuddin, Alimuddin; Widanarni, Widanarni; Nuryati, Sri
Abstract: This study aimed to compare the phenotypic and genotypic characteristics, and pathogenicity of Edwardsiella ictaluri derived from several catfish farming in Indonesia. The isolated bacteria were from West Java, East Java, South Sumatra, Jambi, Lampung, Riau and South Kalimantan. The phenotypic analysis based on conventional biochemical characteristics, API 20E and enzyme activity by APIzym showed that the E . ictaluri from various locations in Indonesia had the different growth patterns, ability to hydrolyze sugar (saccharose and amylase), hydrolyzed gelatin, lysed blood agar media and leucine and valine arylamidase enzyme activity. The sensitivity antibiotic testing showed most of the tested isolates were multi‐drug resistance to five antimicrobial classes (macrolides, lincosamides, rifamycin, penicillins and quinolones). The phylogenetic analysis with sequencing 16S rRNA had 99.56%–100% similarity to E . ictaluri . The genotypic analysis of the similarity strains with Genetic Fingerprinting Repetitive sequence‐mediated PCR (Rep‐PCR) denoted different genotype profiles of each primer ERIC 1 ERIC II, BOX and GTG5 . The protein profiles were analysed using the SDS‐PAGE method. The whole‐cell isolates of E . ictaluri coded PJbH, P and PBm1G had outer membrane protein (OMP) and riboflavin biosynthesis protein (RibD). The pathogenicity test led to high mortality for 97.78%–100% in the whole‐cell treatment, while the low mortality was 6.67% in the ECP treatment. These results concluded that E . ictaluri isolates from various farming in Indonesia had different phenotypic and genotypic variations and protein components of E . ictaluri cells proved to be virulent and played a role in the pathogenesis of E . ictaluri infection in catfish.